2017
DOI: 10.20884/1.sb.2017.4.1.381
|View full text |Cite
|
Sign up to set email alerts
|

KORELASI KARAKTER ANATOMI DAUN UBI JALAR (<em>Ipomoea batatas</em> L.) KULTIVAR TAHAN DAN TIDAK TAHAN TERHADAP INTENSITAS PENYAKIT KUDIS DAUN

Abstract: Sweet potato (Ipomoea batatas L.) is one of alternative food sources beside than rice. Sweet potatoes are contains minerals, nutrients, sources of energy, protein, vitamins A and C. Sweet potatoes have lower productivity than rice and cassava. The low productivity of sweet potatoes due to several factors, which one of them is a leaf scab disease caused by pathogens Sphaceloma batatas Saw. The purpose of this study is to determine the character of the anatomy of sweet potato leaf cultivars that resistant and un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 3 publications
0
4
0
3
Order By: Relevance
“…Arifin (2013) adds that the number of trichomes in healthy soybean plants is higher more than in sick soybean plants. Pradana et al (2017) reported that the density of stomata-trichomes was the same as the plant disease intensity. On the other hand, Samiyarsih et al (2020b) mention that soybean cultivars that have thicker cuticle and epidermis, high trichomes and low stomatal density, and low stomatal conductance have better anatomical resistance to leaf rust disease.…”
Section: Resultsmentioning
confidence: 98%
“…Arifin (2013) adds that the number of trichomes in healthy soybean plants is higher more than in sick soybean plants. Pradana et al (2017) reported that the density of stomata-trichomes was the same as the plant disease intensity. On the other hand, Samiyarsih et al (2020b) mention that soybean cultivars that have thicker cuticle and epidermis, high trichomes and low stomatal density, and low stomatal conductance have better anatomical resistance to leaf rust disease.…”
Section: Resultsmentioning
confidence: 98%
“…Tanaman lada yang terinfeksi penyakit melakukan transpirasi untuk mempercepat laju pengangkutan unsur hara dari akar menuju daun, semakin cepat laju transpirasi berarti semakin cepat pengangkutan air dan zat hara terlarut (Silaen, 2021). Agar tidak terjadi transpirasi yang berlebihan pada tanaman, stomata menurunkan tekanan turgor dengan cara menutup stomata (Pradana et al, 2017). Stomata pada tanaman lada yang terinfeksi penyakit menurunkan tekanan turgor sel penjaga sehingga ukuran stomata menjadi kecil (Bertolino et al, 2019).…”
Section: Hasil Dan Pembahasanunclassified
“…Namun adanya infeksi penyakit ini diduga memiliki keterkaitan dengan penebalan kutikula dan epidermis meskipun tidak terlalu besar, hanya sekitar 10,25-18,95%, hal ini karena tanaman lada yang mengalami infeksi patogen di bagian perakarannya sehingga menyebabkan terhambatnya serapan hara dan mineral yang dibutuhkan tanaman untuk pertumbuhan dan perkembangan tanaman (Suryanti et al, 2017). Kutikula dan epidermis yang menebal merupakan bentuk adaptasi ketahanan struktural untuk menghambat infeksi patogen, karena kedua lapisan ini bersifat membatasi ruang interseluler (Pradana et al, 2017). Kutikula dan epidermis berfungsi melindungi jaringan dari lingkungan luar.…”
Section: Hasil Dan Pembahasanunclassified
“…Ecological factors are closely related to the leaf anatomical characteristic (He et al 2017). The density of stomata-trichomes and cuticle thickness of sweet potatoes leaves correlated with the intensity of leaf scab disease caused by pathogens Sphaceloma batatas (Pradana et al 2017). Samiyarsih et al (2020) reported that different cultivars of one species almost gave different structures, phytochemical compounds, and different biological activities.…”
Section: Anatomical Profile Of Paradermal Sectionmentioning
confidence: 99%